Management of Surgical Instruments in Geriatric Patients Undergoing Decompressive Craniectomy: A Case Report - Ariani Nur Syawali; Ida Ayu Dewi Sandhyagandhi; Nyoman Agus Jagat Raya (Health and Technology Journal (HTechJ), 2026)
Ensuring the safety of elderly patients undergoing decompressive craniectomy is crucial due to the high risk of complications resulting from surgical instrument mismanagement. This study aims to evaluate instrument management in elderly patients through a single case study approach. The method involved direct observation and interviews with the medical team during the surgical procedure, focusing on the implementation of the surgical safety checklist. The findings indicate that thorough verification, supervision, and documentation of instruments before, during, and after surgery play a significant role in preventing medical errors, improving surgical team efficiency, and accelerating patient recovery. The study concludes that the structured application of checklists significantly enhances patient safety in elderly individuals. It is recommended that all surgical team members, especially operating room nurses, consistently perform verification and monitoring of instruments to reduce the risk of complications and improve the quality of surgical care.